Eunapius of Sardis - Buck, D; David F. Buck (1978)
﻿ Eunapius of Sardis was a pagan Greek sophist and historian who lived from A.D. 345/6 until at least A.D. 414. Two of his works survive. The Lives of the Philosophers and Sophists is complete, but the Histories, which covered the period from A.D. 270 to A.D, 404, are fragmentary. This thesis falls into four parts. The first deals with Eunapius' family, education, and role as a sophist and the second examines the Lives in relation to other pagan and Christian biographies of this type. Part III is concerned with the reconstruction and formal characteristics of the Histories and Part IV demonstrates Eunapius' practice as an historian. Sardis was the metropolis of Lydia and prosperous enough to undertake an extensive re-building programme c. A.D. 400 when the defences were strengthened and the two main streets were paved and colonnaded with marble. It was a major Christian centre, but there were also an important Jewish community and a considerable pagan element. From the evidence of Eunapius' education and later life, his family seems to have belonged to the curial class and to have had at least moderate means. Eunapius was taught first at Sardis by Chrysanthius and went to Athens in his sixteenth year where he studied under Prohaeresius for five years. He then returned to Sardis and studied philosophy with Chrysanthius, for he was a Neoplatonist and a member of the school of Pergamon which traced its descent from Iamblichus. Eunapius also possessed a good enough knowledge of medicine to be regarded as a iatrosophist. In his later life, he appears to have been a gentleman sophist and historian who was familiar with the upper echelons of the provincial government, although he believed that a sophist's first loyalty was to his native city and he disapproved of imperial service, particularly by philosophers. Eunapius wrote the Lives c. 400, partly for didactic purposes, but more to commemorate Chrysanthius and Prohaeresius and to counter Christian hagiography. However, an examination of pertinent works shows that Eunapius owed nothing to Christian hagiography. On the formal level, the Lives combine the features of Sotion's Succession and Philostratus' Lives of the Sophists; on the spiritual level, Eunapius is most clearly indebted to Philostratus' Life of Apollonius of Tyana. Part III is largely concerned with the reconstruction of the Histories. The most important fragments are found in the Constantinian Eclogues de Sententiis and de Legationibus and these are dealt with first along with later historians for whom Eunapius was a source. (Such evidence as there is indicates that Ammianus Marcellinus used Eunapius.) Zosimus is the most important guide to the bias and content of the Histories since his New History from I,47 to V,25 depends exclusively upon Eunapius. A number of anonymous fragments in the Suda have been attributed to Eunapius and these are discussed in some detail. An outline reconstruction of the Histories on a regnal basis is then attempted and a solution for the problem of the second edition is proposed. Eunapius must have written both editions himself and have ended both in 404. Finally, the Histories are put in their formal context: Eunapius continued Dexippus, but his closest model appears to be Herodian. Eunapius' Histories were the canonical pagan Greek account of the fourth century A.D. and a major component of the Hellenic reaction against Christianity. Eunapius had good information, particularly for the east, and in his statements about his sources and other aspects of historiography he is similar to contemporary historians like Ammianus, However, he often distorted or suppressed facts in order to protect or to demonstrate his belief in pagan Providence. This is revealed by an examination of how he defamed Constantine and Theodosius (who are held principally responsible for the decline of the Roman empire) and made Julian the Apostate the hero of his Histories. The main feature of the account of Constantine is that it is constructed to fit a date of 326 for the emperor's guilt-ridden conversion to Christianity. Eunapius had to be more subtle in dealing with the contemporary Theodosius, but even so he saecularized the Battle of the Frigidus. Julian, on the other hand, is portrayed as the perfect ruler, a philosopher-king who was protected by Providence throughout his life and apotheosized on his death. The eight appendices provide detailed information in tabular form, except for Appendices V and VIII. The former elucidates the structure and chronology of Palladius' Lausiac History and the latter argues that there was no second edition of the Lives.